A handbook for the art and science of teaching - Marzano, Robert J.; Brown, John L., 1947- (Alexandria, Virginia : Association for Supervision and Curriculum Development, 2009)
"Implementing the action steps from ASCD's best-seller The Art and Science of Teaching is much easier when you use this in-depth resource for workshops, professional learning communities, teacher training, and self-help. Hundreds of samples, guidelines, checklists, and activities help teachers in all grades and subjects become instant experts on Robert Marzano's breakthrough framework for effective instruction. A series of 25 modules equips any classroom teacher with a logical planning sequence that ensures you establish learning goals and track progress, help students interact with new knowledge, test hypotheses, and develop deep understandings, and Establish good classroom management and effective relationships with students. "
Includes bibliographical references.
Keywords: Effective teaching -- Handbooks, manuals, etc